Synthesis, characterization and electropolymerization of a new polypyrrole iron(II) Schiff-base complex - Chiericato, G.; Silva, APS; Guinesi, L. S. (Elsevier B.V., 2004)
This work presents the synthesis of the complex [Fe(L)(2)](PF6)(2) (.) H2O (L = 2,6-bis[1-(3-pyrrol-1-yl-propylimino)ethyl]pyridine (Fig. 1) and its characterization through elemental and thermal analysis, X-ray diffraction and UV-Vis, IR and H-1 NMR spectra. The use of this compound in the preparation of modified electrodes is also described. The best electrochemical parameters to achieve optimum film formation have been established and the effects of both the upper-limit of the applied scanning potential (E-aul) and the number of scans on the efficiency of film formation have been investigated. Film surface morphology has been characterized by atomic force microscopy. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Schiff-base; polypyrrole; electropolymerization; iron complex; AFM; polymer